Insights from ELF and WE in teacher training in Greece and Turkey - Sifakis, N.; Y. Bayyurt (World Englishes, 2015)
The paper describes a framework for the education of ESOL teachers that is inspired by principles grounded in research on English as a lingua franca (ELF) and world Englishes (WE). The essential feature of such a framework is that it involves interested teachers in a critical reorientation of their beliefs toward English language teaching, learning and communication. This transformative framework informs what we call the ‘ELF-aware’ teacher education component. We then present a framework for a transformative perspective for ELF-aware and WE-aware teachers and describe the phases of a teacher education project that attempted to put this framework into practice.